Learning disabilities in Darier's disease patients. (15th February 2013) - Dodiuk‐Gad, R.; Lerner, M.; Breznitz, Z.; Cohen‐Barak, E.; Ziv, M.; Shani‐Adir, A.; Amichai, B.; Zlotogorski, A.; Shalev, S.; Rozenman, D.
Abstract Background Neuropsychiatric features and intellectual difficulties have been reported in studies of Darier's disease. Learning disabilities have never been reported or evaluated systematically in these patients. Objective To assess the prevalence of learning disabilities in 76 patients with Darier's disease, and cognitive functioning in 19 of them. Methods The data were collected by two methods: a questionnaire, as part of a larger study on the clinical characteristics of 76 patients; and neuropsychological measures for the assessment of learning disabilities in 19 of them. Results Thirty‐one of the 76 patients reported learning disabilities (41%) and 56 (74%) reported a family history of learning disabilities. Significant differences were found between the 19 patients evaluated on cognitive tasks and a control group of 42 skilled learners on subtraction and multiplication tasks. Six (32%) of the 19 were identified as having reading difficulties and five (26%) exhibited low performance on the Concentration Performance Test. All patients had general cognitive ability in the average range. Conclusions Findings suggest an association between Darier's disease and learning disabilities, a heretofore unreported association, pointing to the need to obtain personal and family history of such disabilities in order to refer cases of clinical concern for further study.